Does Connectedness Matter? The Association Between Mutuality and Job Satisfaction Among Home Health Aides Caring for Adults With Heart Failure. (April 2023) - Shalev, Ariel; Ringel, Joanna B.; Riegel, Barbara; Vellone, Ercole; Stawnychy, Michael A.; Safford, Monika; Goyal, Parag; Tsui, Emma; Franzosa, Emily; Reckrey, Jennifer; Sterling, Madeline
Home health aides (HHAs) provide care to many adults with heart failure (HF) in the home. As the demand for HHAs increases, there is a need to promote HHAs' job satisfaction and retention. In this cross-sectional community-partnered study, we examined whether mutuality (e.g., quality of the HHA-patient relationship), is associated with job satisfaction among HHAs caring for adults with HF. Mutuality was assessed with the Mutuality Scale, which measures overall mutuality and its four domains (reciprocity, love and affection, shared pleasurable activities, and shared values). Our final sample of 200 HHAs was primarily female. The mean overall mutuality score was 2.92 out of 4 (SD 0.79). In our final model, overall mutuality and each of the four domains were associated with increased job satisfaction; however, only the shared pleasurable activities domain was significant (aPR: 1.15 [1.03–1.32]). Overall, mutuality may play a role in promoting job satisfaction among HHAs.